Visual benefits and complications following neodymium-doped yttrium aluminum garnet (Nd: YAG) capsulotomy - Ajay R Kamath; Gundapaneni, Ramya (Asian Journal of Medical Sciences, 2023)
Background: The incidence of posterior capsule opacification (PCO) noted at the end of 5 years following cataract extraction is 33%. With the advent of phacoemulsification various materials and designs of intraocular lenses, the incidence of PCO has been reduced. Following pediatric cataract surgery, the incidence of PCO was found to be 100%. Nd: YAG capsulotomy is considered a safe, effective, and non-invasive technique to treat PCO. Aims and Objectives: The aim of the study was to evaluate the visual acuity among the patients with PCO and to assess the complications following Nd: YAG capsulotomy. Materials and Methods: A total of 100 eyes of 100 patients with study period being 2 years from October 2015 to July 2017. The study was prospective study, and sampling was purposive sampling. After recruiting, the participants were divided into 2 case groups - pseudophakia and aphakia. A complete ophthalmological evaluation was done which included best-corrected visual acuity, torchlight and slit-lamp examination, and measurement of IOP which was followed by a fundus examination. Results: The minimum and maximum age of the patient observed in our study was 34 and 88. Most of the study population was in the age group of 51–60 years. Majority of patients presented with PCO with an interval of 25–36 months following cataract surgery and were noted in about 52% of study population. Majority of the patients had visual acuity 6/36-6/18 and observed in 36% of study population. Comparison between pre-YAG and post-YAG day 1 visual acuity was done using significance test and P=0.000 which was highly significant, visual acuity at 4th week was compared to that of 6th week, and it was significant. Conclusion: The loss of vision due to PCO is a distressing complication for a patient who has spent time and money getting their surgery done and finds that their vision is dropping again. YAG laser capsulotomy is a simple, outpatient solution that will bring the smile back on the patient’s face instantly. Capsulotomy improves visual acuity immediately after the procedure and more after 4 or 6 weeks with least complications.